A INFLUÊNCIA DOS MECANISMOS DE DEFORMAÇÃO PLÁSTICA NA MEDIDA DE TENACIDADE PELA TÉCNICA DE MICROINDENTAÇÃO EM VIDROS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
This study investigated the effects of Poisson’s ratio on fracture toughness measured by microindentation using the models of Anstis et al. and Niihara et al. Experiments were performed in different oxide glasses with Poisson’s ratio ranging from 0,15 to 0,28. The glass transition temperatures of the glasses were measured by differential scanning calorimetry.. The amorphous state of the glasses were confirmed by X-ray diffraction. Hardness and elastic modulus were measured using instrumented indentation. The fracture toughness values, KIC, were obtained using the double torsion and four point bending techniques. The relation between the applied load and the crack radial length was obtained using the Vickers microindentation technique. It was noted the existence of two systems. For Poisson’s ratio smaller than 0,20, the main deformation mechanism is densification and the calibration coefficients are smaller than those reported in the literature. On the other hand, when the Poisson’s ratio are higher than 0,20, the main deformation mechanism is by shear and the calibration coefficients are higher than those reported in literature.
Keywords: vidros; óxidos; coeficiente de Poisson; tenacidade à fratura; indentação; glass; oxides; Poisson’s ratio; fracture toughness; indentation; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA